Meta Analysis: Effect of Iron Supplement Consumption and Menstrual Duration on Anemia in Adolescent Girls - Guspianto, Guspianto; Kalsum, Ummi; Diastanti, Yunita (Universitas Aisyah Pringsewu, 2025)
Anemia has a negative impact on physical function, especially reproductive organ function in adolescent girls. The prevalence of anemia in adolescent girls globally is still high at 29.6%, including in Indonesia at 32%. This study aims to analyze findings from studies related to the prevalence of anemia and consumption of iron supplements and the duration of menstruation in adolescent girls. The research design uses a systematic review with meta-analysis of articles that sourced from three databases, namely Google Scholar, Pubmed, and Scopus. Search for articles using Publish or Perish software, and selected according to inclusion criteria, namely Indonesian or English language, full-text from 2013 to 2022, cross-sectional study design with the adjusted odds ratio measure. The data analysis using RevMan 5.4. Total of 10 articles met the inclusion criteria from 11,425 articles identified. The average prevalence of anemia in adolescent girls was 34.55% (CI 95%: 19.49-49.60). The results of the meta-analysis showed that iron supplement consumption (aOR= 6.17; 95% CI= 1.66-22.93; P-value 0.01) and menstrual duration (aOR= 5.97; 95% CI= 3.60-27.66; P- value= 0.04) influences the incidence of anemia in adolescent girls. It is recommended that young women always consume iron supplements according to government programs, especially during menstruation.